Facilitating effective management of classroom learning in Nigerian school (2011)
Learning takes place with cooperation between teachers and learners using established norms. Certain variables have been identified as contributory to effective teaching and learning in Nigerian schools among which are; teaching materials that include knowledge generation and its utilisation, pedagoogical principles that include teacher preparation, infrastructural provision and development involving school plant creation, classroom creation, class size and general management of the classroom. Classroom management has peculiar challenges in the present dispensation. The study gives an overview of knowledge creation znd its management, learning principles and general thoeries of learning. It investigates challenges and causes of poor classroom learning of include; inadequate teacher preparation, inadequate instructional materials for effective classroom instruction in schools, uncooperative ethnic divergences on the perception of education, poverty that induces absenteesim and indiscipline in schools, unfriendly educational policies orchestrated by forces of ethnicism, nepotism, poor leadership and corruption. Other challenges include increasing dissatisfaction with the returns to education. Solutions advocated include; sensitization of stakeholders on the need to educated citizens and see internal education as a product that must be jointly funded by private and public sector, increas in training and retraining of staff (teachers) to meet present needs of the school system, class size, pupil/teacher ratios, infrastructural provision etc. Perspectives of 21st century effective classroom management are examined.